A problem of "Raseiniai tank's" history - Arvydas Žardinskas (Lietuvos Istorijos Studijos)
During the opening days of the German-Soviet war in the area of Raseiniai, one of the largest tank battles took place. One episode of this battle is the so-called history of the tank of Raseiniai. This episode of the initial period of the war was researched by some historians, but almost all of them used the same sources. Therefore, we can find some misconstructions (e.g., that this panzer battle lasted two or even three days), and sometimes even solid authors make basic geographical mistakes.